2001
DOI: 10.1074/jbc.m101054200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Adaptor Protein-1 of the Clathrin Coat and Microtubules via Type 1a Microtubule-associated Proteins

Abstract: The classical view suggests that adaptor proteins of the clathrin coat mediate the sorting of cargo protein passengers into clathrin-coated pits and the recruitment of clathrin into budding areas in the donor membrane. In the present study, we provide biochemical and morphological evidence that the adaptor protein 1 (AP-1) adaptor of the trans-Golgi network clathrin interacts with microtubules. AP-1 in cytosolic extracts interacted with in vitro assembled microtubules, and these interactions were inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Consistent with this notion, AP-1 interacts with microtubules and coimmunoprecipitates with microtubule-associated proteins (Orzech et al, 2001). Furthermore, ciliary microtubule acetylation defects are found in mammalian cells overexpressing Rab8(wt) or Rab8-GTP (Nachury et al, 2007), which is relevant to AP-1 based on our findings (discussed below) that AP-1 and RAB-8 function in a common ciliary membrane transport pathway in C. elegans.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with this notion, AP-1 interacts with microtubules and coimmunoprecipitates with microtubule-associated proteins (Orzech et al, 2001). Furthermore, ciliary microtubule acetylation defects are found in mammalian cells overexpressing Rab8(wt) or Rab8-GTP (Nachury et al, 2007), which is relevant to AP-1 based on our findings (discussed below) that AP-1 and RAB-8 function in a common ciliary membrane transport pathway in C. elegans.…”
Section: Discussionsupporting
confidence: 66%
“…Our observations suggested that vesicle trafficking might be affected by MB since proteins which mediate transport between ER and Golgi such as SEC22b, STX5, KDELR2 and ERGIC1 [75,76,78] and VPS16 and GGA3 between Golgi and the endosomes [79,80] were up-regulated. On the other hand, proteins such as: VAMP3, a vesicle-associated membrane protein involved in regulating membrane traffic; AP1S2, modulating the dynamics of the cytoskeleton [81]; and GOSR2 involved in transport of proteins from the cis/medial-Golgi to the trans-Golgi network [75]; were down-regulated by MB.…”
Section: Discussionmentioning
confidence: 99%
“…There are at least four distinct adaptor protein (AP) complexes that link clathrin to membranes, coordinate clathrin coat assembly, and recruit cargo proteins. AP-1 functions in multiple steps in vesicle trafficking and cargo sorting from the Golgi to endosomes and the plasma membrane and is critical for the sorting and recycling of receptors to correct plasma membrane domains (Futter et al 1998;Nakagawa et al 2000;Orzech et al 2001;Gan et al 2002;Pagano et al 2004). The m-chain of AP-1 appears to be responsible for sorting cargo proteins into developing vesicles.…”
Section: Bmps4mentioning
confidence: 99%